2010
DOI: 10.1080/08870440802559375
|View full text |Cite
|
Sign up to set email alerts
|

Does change in positive affect mediate and/or moderate the impact of symptom distress on psychological adjustment after cancer diagnosis? A prospective analysis

Abstract: Physical symptom distress is one of the commonest correlates of psychological adjustment in cancer patients. Positive affect (PA) can be a dynamic resource for patients to cope with the cancer-related physical demands. The present study examined whether differential patterns of change in PA were associated with anxiety and depressed mood, and whether PA modified the association between change in symptom distress and psychological distress in 215 Chinese people newly diagnosed with colorectal cancer (CRC). Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 49 publications
1
48
0
1
Order By: Relevance
“…One of our previous studies developed a psychometric instrument for assessing multiple dimensions of relationship quality that are significantly associated with psychosocial functioning of Chinese CRC patients, namely Family Intimacy-empathy and closeness through day-to-day emotions and activities, and secure attachment to family at critical times; Family Commitment-determination to maintain satisfying and enjoyable family relationships; and Friendships-positive relationships and interactions with friends [27]. We have also reported the adaptation process in these people [28][29][30][31]. Apart from perceiving a sense of personal control over cancer-related problems, Chinese CRC patients also reported a separate sense of control, i.e., collective control in collaboration with close social partners.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…One of our previous studies developed a psychometric instrument for assessing multiple dimensions of relationship quality that are significantly associated with psychosocial functioning of Chinese CRC patients, namely Family Intimacy-empathy and closeness through day-to-day emotions and activities, and secure attachment to family at critical times; Family Commitment-determination to maintain satisfying and enjoyable family relationships; and Friendships-positive relationships and interactions with friends [27]. We have also reported the adaptation process in these people [28][29][30][31]. Apart from perceiving a sense of personal control over cancer-related problems, Chinese CRC patients also reported a separate sense of control, i.e., collective control in collaboration with close social partners.…”
Section: Introductionmentioning
confidence: 75%
“…A study of Chinese women with gynecologic cancers has demonstrated a link between social relationships and satisfaction with life; however, a small sample size (n=62) and the use of non-validated measure to assess satisfaction with life (i.e., a single item) limit generalizability and conclusiveness of the findings [68]. Our previous study has reported that change in positive affect mediates the negative impact of physical symptom distress on Chinese CRC patients [30]. This study extends previous studies by using an adequate sample of Chinese patients (n=234), one of the largest samples in psycho-oncology research with Chinese.…”
Section: Limitations and Conclusionmentioning
confidence: 88%
See 1 more Smart Citation
“…Estudos apontam que o diagnóstico de câncer provoca uma ruptura na vida da pessoa adoecida (Hou, Law & Fu, 2010 …”
Section: Sentido Da Experiência De Ser Cuidadorunclassified
“…The main purpose of any psychological intervention in patients diagnosed with cancer is to aid toleration of the diagnosis and treatment, decreasing the feelings of defencelessness and abandonment, reducing the anxiety related to the treatments, and clarifying any erroneous information and perceptions (Dempster, McCorry, Brennan, Donnelly, Murray & Johnston, 2011;Dobkin & Costa, 2000;Hou, Law & Fu, 2010;Novoa, Vargas, Obispo, Petrus & Rivera, 2010;Pinquart & Fröhlich, 2009) 32, 33, 34, 35, 36) . According to Bárez, et al (2003) 37) , the strategies that are carried out in this type of situation are related to emotional support, in terms of the patient feeling that they are being listened to, understood, encouraged and well cared for, to educational-informational support, which favours the necessary level of information to be able to handle the whole process, and to instrumental support, where the patients are provided with different economic and material resources or with home assistance.…”
mentioning
confidence: 99%